Effects of a community-based pulmonary rehabilitation programme during acute exacerbations of chronic obstructive pulmonary disease - a quasi-experimental pilot study - Machado, A. (2020)
Background: Pulmonary rehabilitation (PR) is a cornerstone intervention for the management of patients with stable chronic obstructive pulmonary disease (COPD). However, its role during acute exacerbations (AECOPD) is controversial since most studies have been conducted in hospitalised patients, when more than 80% of AECOPD are managed on an outpatient basis. This quasi-experimental pilot study assessed the effects of a community-based PR programme during mild-to-moderate AECOPD. Methods: Outpatients were recruited from hospitals and allocated to experimental (EG) or control (CG) groups. EG received standard medication plus 3-weeks of PR. The CG received standard medication. Dyspnoea (mMRC), quadriceps muscle strength (QMS), functionality (5-repetition sit-to-stand test) and impact of the disease (COPD assessment test (CAT)) were assessed within 48 h of the AECOPD onset and after PR. Symptoms of dyspnoea and fatigue (mBorg), heart and respiratory (RR) rates and peripheral oxygen saturation (SpO2) were assessed at rest and monitored in all PR sessions. Need for hospitalisation was monitored during the 3-weeks. Results:Twelve patients (69 ± 7 years, FEV1 52 ± 27 pp) in the EG and eleven in the CG (66 ± 9 years, FEV1 55 ± 22 pp) were enrolled. The EG presented significant improvements on QMS (Pre 21.0 vs. Post 25.0, p = 0.012), CAT (Pre 23.0 vs. Post 14.5, p = 0.008), symptoms of dyspnoea at rest (Pre 3.0 vs. Post 1.0, p = 0.008), SpO2 (Pre 94.0 vs. Post 96.0, p = 0.031) and RR (Pre 24.0 vs. Post 20.5, p = 0.004). No significant improvements were found in the CG.